1986
DOI: 10.1111/j.1471-4159.1986.tb13049.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Uric Acid Level in Rat Brain After Focal Ischemia

Abstract: Changes of uric acid level in rat cerebral hemisphere after left middle cerebral artery (MCA) occlusion were studied by reversed-phase HPLC with electrochemical detection. Uric acid level in the normal group was 2.98 nmol/g tissue. Uric acid concentration of the left hemisphere in the left MCA-occluded group progressively increased after occlusion, and reached a maximum value of 67.26 nmol/g tissue 24 h after ischemia. Uric acid levels in the right hemisphere remained unchanged. Uric acid concentration of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 12 publications
3
13
0
Order By: Relevance
“…In the present study, UA 24 h after focal ischaemia was observed to increase approximately 13-fold over nonischaemic hemisphere levels. This increase is consistent with those observed in other studies [11,12,24].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the present study, UA 24 h after focal ischaemia was observed to increase approximately 13-fold over nonischaemic hemisphere levels. This increase is consistent with those observed in other studies [11,12,24].…”
Section: Discussionsupporting
confidence: 83%
“…UA accumulation in the CSF during pathological conditions was reported by Haelergen and coworkers, who speculated in 1983 that this indicates only a dysfunction of the blood-brain barrier [8]. A new quantitative method using HPLC equipped with an electrochemical detector reported an increase in UA concentration in the ischaemic brain [11].…”
Section: Discussionmentioning
confidence: 97%
“…30 Uric acid, the product of the reaction xanthine oxidase catalyzes, accumulates in ischemic rat brain. 31 Further, xanthine oxidase is enriched in rat brain capillaries relative to whole brain. 12 Therefore, in addition to reducing generalized free radical injury, inhibiting xanthine oxidase could be expected to specifically preserve capillary function.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a high uric acid level is known effect of alcohol metabolism and thus, hyperuricemia may be found in alcoholic liver disease 5,6 . In different biological studies, UA levels have been found to correlate directly with the level of tissue damage 7 . Compared to the serum levels, the tissue levels of UA may be even better predictors of tissue injury 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In different biological studies, UA levels have been found to correlate directly with the level of tissue damage 7 . Compared to the serum levels, the tissue levels of UA may be even better predictors of tissue injury 7 . Thus, UA may be considered as a marker of tissue damage.…”
Section: Introductionmentioning
confidence: 99%